Efficacy and safety of different regimens in the treatment of patients with latent tuberculosis infection: a systematic review and network meta-analysis of randomized controlled trials - Dawit Getachew Assefa; Ahmed Bedru; Eden Dagnachew Zeleke; Solomon Emiru Negash; Dejene Tolossa Debela; Wondowsen Molla; Nebiyu Mengistu; Tigist Tekle Woldesenbet; Neway Fekede Bedane; Violet Dismas Kajogoo; Mary Gorret Atim; Tsegahun Manyazewal (BMC, 2023)
Abstract Background Treatment of latent tuberculosis infection (LTBI) is effective in preventing progression to TB disease. This study aimed to synthesize available evidence on the efficacy, adherence, and safety of LTBI treatment in order to assist policymakers to design appropriate national treatment policies and treatment protocols. Method The PRISMA-NMA was used to review and report this research. Randomized controlled trials which compared the efficacy and safety of LTBI treatments were included. A systematic literature search was done to identify relevant articles from online databases PubMed/ MEDLINE, Embase, and Cochrane Center for Clinical Trial database (CENTRAL). The network meta-analysis was done using R- studio Version 1.4.1103. Result In this review, 42 studies were included, which enrolled 46,022 people who had recent contact with patients with active tuberculosis, evidence radiological of previous tuberculosis, tuberculin test equal or greater than 5 mm, radiographs that indicated inactive fibrotic or calcified parenchymal and/or lymph node lesions, had conversion to positive results on a tuberculin skin test, participants living with HIV, chronic Silicosis, immigrants, prisoners, old people, and pregnant women who were at risk for latent TB were included. The incidence of TB among people living with HIV who have taken 3RH as TPT was lower, followed by 48%,followed by 6H (41%). However, 3HP has also the potential to reduce the incidence of TB by 36% among HIV negative patients who had TB contact history. Patients' adherence to TPT was higher among patients who have taken 4R (RR 1.38 95% CI 1.0,1.89) followed by 3RH (34%). The proportion of subjects who permanently discontinued a study drug because of an adverse event were three times higher in the 3RH treatment group. Furthermore, the risk of grade 3 and 4 liver toxicity was significantly higher in 9H followed by 1HP, and 6H. Conclusion From this review, it can be concluded 3RH and 6H has a significant impact on the reduction of TB incidence among PLWH and 3HP among HIV negative people who had TB contact history. However, combinations of rifampicin either with isoniazid were significantly associated with adverse events which resulted in permanent discontinuation among adult patients. Furthermore, grade 3 and 4 liver toxicity was more common in patents who have taken 9H, 1HP, and 6H. This may support the current recommended TPT regimen of 3HP, 3RH, and 6H.